2007
DOI: 10.1007/s00436-007-0727-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional surveys and subtype classification of human Blastocystis isolates from four epidemiological settings in China

Abstract: The prevalence and geographical distribution of the intestinal protozoa Blastocystis in humans across China is unknown, and the relative importance of different subtypes has yet to be investigated. We assessed the community prevalence and relative frequencies of different Blastocystis subtypes in four epidemiological settings in China, i.e., Shanghai municipality, Yongjia county (Zhejiang province), Eryuan county, and Menghai county (both Yunnan province). Blastocystis infection was detected with the culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
74
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 28 publications
12
74
1
2
Order By: Relevance
“…infection. 9 However, other studies found no significant relation between the infection prevalence and age. 38,39 These contradictory results can be explained by the local determinants such as the environmental conditions that affect the fecal-oral route of transmission among individuals of different ages and genders.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…infection. 9 However, other studies found no significant relation between the infection prevalence and age. 38,39 These contradictory results can be explained by the local determinants such as the environmental conditions that affect the fecal-oral route of transmission among individuals of different ages and genders.…”
Section: Discussionmentioning
confidence: 92%
“…comprises at least 17 subtypes (STs) nine of which have been reported in humans. [6][7][8][9][10][11] Pathogenesis of blastocystosis still remains uncertain, as the organisms can be found in both symptomatic and asymptomatic patients. 6 It has been proposed that the pathogenesis of Blastocystis spp.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that the high prevalence of Blastocystis hominis in the current study (up to 27%) is consistent with reports of up to 33% prevalence of this parasite in China. 58 Data in vitro suggest that Blastocystis hominis may induce inflammatory cytokines in the host' s gut epithelial cells. 59 No differences in the prevalence of this parasite were seen between groups at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…According to a report by the world health organization (WHO), about three billion of world population is infected with intestinal parasite [3,4] and 450 million people, including children experience the adverse effects of intestinal parasitic disease [5]. A careful perusal of literature indicates that the prevalence rate of intestinal parasite infection is 7% -20% in developed countries while 30% -60% children in rural areas are affected by parasite infection in these countries [6][7][8][9][10][11]. Malnutrition, diarrhea, weight loss, anemia pose a mortal threat to human populations and cause about 16 million deaths in the developing countries every year [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%